Two Zetas in One

Calculus Level 5

p = prime ( 1 1 p 1 + 1 1 + p 1 1 ) \prod_{p= \text{prime}} \left(\frac{1}{1-p^{-1}} + \dfrac{1}{1+p^{-1}} - 1\right)

Find the value of the closed form of the above product.


The answer is 2.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Relevant wiki: Riemann Zeta Function

According to Riemann Zeta function , the product of prime p p can be written in a form:

ζ ( s ) = p = p r i m e 1 1 p s . \zeta(s)=\prod_{p=prime} \dfrac{1}{1-p^{-s}}.

Then we need to rearrange the original expression into a more applicable form:

p = p r i m e ( 1 1 p 1 + 1 1 + p 1 1 ) = p = p r i m e ( p p 1 + p p + 1 1 ) = p = p r i m e ( 2 p 2 p 2 1 1 ) = p = p r i m e ( p 2 + 1 p 2 1 ) \prod_{p=prime} (\dfrac{1}{1-p^{-1}} + \dfrac{1}{1+p^{-1}} - 1) = \prod_{p=prime} (\dfrac{p}{p-1} + \dfrac{p}{p+1} - 1) = \prod_{p=prime} (\dfrac{2p^2}{p^2 -1} -1) = \prod_{p=prime} (\dfrac{p^2 +1}{p^2 -1})

Dividing the numerator and the denominator with p 2 p^2 :

p = p r i m e ( p 2 + 1 p 2 1 ) = p = p r i m e ( 1 + p 2 1 p 2 ) \prod_{p=prime} (\dfrac{p^2 +1}{p^2 -1}) = \prod_{p=prime} (\dfrac{1 + p^{-2}}{1- p^{-2}})

Then multiplying both with 1 p 2 1-p^{-2} :

p = p r i m e ( 1 + p 2 1 p 2 ) = p = p r i m e ( 1 p 4 ( 1 p 2 ) 2 ) \prod_{p=prime} (\dfrac{1 + p^{-2}}{1- p^{-2}}) = \prod_{p=prime} (\dfrac{1 - p^{-4}}{(1- p^{-2})^2})

Hence, this is in a form of ( ζ ( 2 ) ) 2 ζ ( 4 ) = ( π 2 6 ) 2 90 π 4 = 2.5 \dfrac{(\zeta(2))^2}{\zeta(4)} = (\dfrac{\pi^2}{6})^2 \dfrac{90}{\pi^4} = \boxed{2.5}

J Joseph
Jan 19, 2017

Unlike Worranat Pakornrat I had a sloppy beginning

p ( 1 1 p 1 + 1 1 + p 1 1 ) \prod _{p} \left ( \frac{1}{1-p^{-1}} + \frac{1}{1+p^{-1}} - 1 \right )

= p ( n = 0 ( ( 1 p ) n + ( 1 p ) n ) 1 ) = \prod_{p} \left ( \sum_{n=0}^{\infty} \left ( \left(\frac{1}{p} \right )^{n} + \left (- \frac{1}{p}\right )^{n}\right)-1 \right )

= p ( 2 n = 0 ( 1 p 2 n ) 1 ) = \prod_{p} \left ( 2\sum_{n=0}^{\infty} \left ( \frac{1}{p^{2n}} \right ) - 1\right)

= p ( 2 ( p 2 p 2 1 ) 1 ) = \prod_{p}\left( 2 \left( \frac{p^{2}}{p^{2} - 1} \right ) - 1 \right )

= p ( 2 p 2 p 2 1 1 ) = p ( p 2 + 1 p 2 1 ) = \prod_{p} \left ( \frac{2p^{2}}{p^{2} - 1} - 1\right ) = \prod_{p} \left ( \frac{p^{2} + 1}{p^{2} - 1}\right)

I then proceeded as Worranat. I am aware that I most likely made many mistakes along the way, regardless, this is my "reasoning".

My answer is 5/2 = 2.5!!! I am correct....

Dim Val - 12 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...